KELAYAKAN MEDIA AUDIO VISUAL DALAM MENULIS TEKS ANEKDOT SISWA KELAS X SMA N 2 LUBUK PAKAM - Adelia Rafita; Ali Ali; Ratna Soraya (Jurnal Dialect, 2025)
This study aims to develop and test the feasibility and effectiveness of audio-visual media in improving the writing skills of anecdotal texts of class X students of SMA N 2 Lubuk Pakam. The population of students is 394 students and the sample taken is 36 students, namely class X-F. This type of research is Research and Development (R&D) using the ADDIE model and method adapted and developed by Reiser and Mollenda in the 1990s, namely, analysis, design, development, implementation, and evaluation. The results of this study indicate that audio-visual media in improving the writing skills of anecdotal texts of class X students of SMA N 2 Lubuk Pakam are classified as very feasible. The assessment of the level of validity of audio-visual media by material expert I obtained an average of 92.67% with the qualification "very valid", by material expert II obtained an average of 80.67% with the qualification "valid". Then the validity assessment by design expert I was 80% with the qualification "valid" by design expert II 86% with the qualification "very valid". Then a trial was conducted on teachers and students, the Indonesian language teacher obtained an overall average score of 98% with the qualification "very worthy" and students also gave a positive and good response by showing an average score of 91% with the qualification "very worthy". Based on this assessment, it can be concluded that audio-visual media in improving the writing skills of anecdotal texts of class X students of SMA N 2 Lubuk Pakam is valid and worthy of use in learning.